STUDI KELAYAKAN PEMBANGUNAN APARTEMEN DI JL. JATIBENING RAYA, PONDOKGEDE, KOTA BEKASI - Jeremia Josiah; Priyendiswara Agustina Bela; B. Irwan Wipranata; Bambang Deliyanto (Jurusan Arsitektur dan Perencanaan, 2020)
Property development growth are still continue to increase in Indonesia, especially in the city of Jakarta which causes land limitations and land values to increase that make property development trend especially residential areas such as apartment has begun shift to buffer city area. Development of residential area is also supported by growth population in Indonesia that increased quite high so the need for residence also increase. Bekasi is one of the buffer city of Jakarta which already has good infrastructure especially in the transportation sector and currently under construction for Cawang-East Bekasi LRT line which will further improve the accessibility of transportation to/form of city of Bekasi. By looking at that opportunities, an apartment development is planned on the vacant land located at Jl. Jatibening Raya, Jatibening Baru, Pondokgede, city of Bekasi. The location of the land is within the planned radius of the 2 LRT stations and the trend of apartment development that has occurred over the last 5 years around the location of the land also provides opportunities for apartment development in the land of object study which is targeted at commuters, also millennials generation. The purpose of this feasibility study is to determine the feasibility of an apartemen development based on a relatively small area of land object study to know the potential and weaknesses. Feasibility of development is seen through analysis on legality, technical and investment aspects that carried out using qualitative methods. The results of this feasibility study are to provide recommendation of feasibility development from alternative product compositions that can provide the best return on investment. Keywords: apartment; development; feasibility study; investment AbstrakPertumbuhan pengembangan properti yang terus meningkat di Indonesia, terutama pada kota Jakarta menyebabkan terjadinya keterbatasan lahan dan naiknya nilai lahan sehingga membuat tren pengembangan properti khususnya kawasan hunian seperti apartemen mulai bergeser ke daerah kota – kota penyangga. Pengembangan kawasan hunian juga didorong oleh peningkatan penduduk yang cukup tinggi di Indonesia sehingga kebutuhan akan hunian juga semakin meningkat. Kota Bekasi merupakan salah satu kota penyangga dari kota Jakarta yang sudah memiliki infrastruktur cukup baik terutama di sektor transportasi dan saat ini sedang dilakukan pembangunan jalur LRT Cawang-Bekasi Timur yang akan semakin meningkatkan kemudahan aksesibilitas transportasi dari/menuju kota Bekasi. Dengan melihat peluang yang ada, maka direncanakan pembangunan apartemen pada objek lahan kosong yang terletak di Jl. Jatibening Raya, Kel. Jatibening Baru, Kec. Pondogede, Kota Bekasi. Lokasi lahan yang berada dalam radius rencana dari 2 stasiun LRT dan tren pembangunan apartemen yang terjadi selama 5 tahun terakhir di sekitar lahan pengembangan juga memberikan peluang untuk pembangunan apartemen pada objek studi yang ditargetkan untuk para commuter, termasuk para generasi milenial. Tujuan studi kelaykan ini adalah untuk mengetahui kelayakan pembangunan apartemen yang didasarkan pada luas lahan yang relatif kecil, agar dapat mengetahui potensi dan kelemahan yang ada. Kelayakan dilihat melalui analisis pada aspek legalitas, teknis dan investasi yang dilakukan menggunakan metode kualitatif. Hasil studi kelayakan ini adalah memberikan rekomendasi kelayakan pembangunan dari alternatif komposisi produk yang dapat memberikan pengembalian investasi terbaik.